2010
DOI: 10.1007/s00586-010-1488-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of adhesion formation and promotion of wound healing after laminectomy by pharmacological inhibition of pro-inflammatory cytokines: an experimental study in the rat

Abstract: In a previous experiment using TNF inhibition in the rat it was accidentally found that adhesion and scar formation was reduced compared to previous experience. Wound and bone healing also seemed enhanced. The present study was conducted to assess if this observation could be verified in a controlled setting using a standardized laminectomy in the rat. Five rats received doxycycline and five other rats received saline and served as control. Macroscopic blinded evaluation 1 week after the laminectomy revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…As concerns about adhesion and its clinical significance increased, Holtz [19] proposed a five-phase method to reduce adhesion: (1) reducing the initial inflammatory reaction and subsequent exudate release; (2) inhibiting coagulation of this exudate; (3) promoting the removal of fibrin deposition; (4) mechanically separating fibrincovered surfaces; and (5) inhibiting fibroblastic proliferation. As attempts to reduce the initial inflammatory reaction and the exudates release, various methods were used: alteration of surgical methods such as microdiscectomy [20], use of anti-inflammatory medications [21,22]. Bio and synthetic substances such as fat [3,23,24], Gel form and Avitene [21], Silastic [3], Polylactic acid [7], Gore-Tex membranes [25] were used based on a theoretical background that they can separate the nerve tissue (the dura and nerve roots) from its surrounding tissues (the paraspinal muscles and periosteum).…”
Section: Discussionmentioning
confidence: 99%
“…As concerns about adhesion and its clinical significance increased, Holtz [19] proposed a five-phase method to reduce adhesion: (1) reducing the initial inflammatory reaction and subsequent exudate release; (2) inhibiting coagulation of this exudate; (3) promoting the removal of fibrin deposition; (4) mechanically separating fibrincovered surfaces; and (5) inhibiting fibroblastic proliferation. As attempts to reduce the initial inflammatory reaction and the exudates release, various methods were used: alteration of surgical methods such as microdiscectomy [20], use of anti-inflammatory medications [21,22]. Bio and synthetic substances such as fat [3,23,24], Gel form and Avitene [21], Silastic [3], Polylactic acid [7], Gore-Tex membranes [25] were used based on a theoretical background that they can separate the nerve tissue (the dura and nerve roots) from its surrounding tissues (the paraspinal muscles and periosteum).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous anti‐adhesion products have been introduced into the commercial market involving pharmacological inhibition and barrier prevention . However, none are composed of natural materials except hyaluronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In a study using a rat laminectomy defect model, rats that received intra-peritoneal doxycycline showed enhanced wound healing, potentially due to reduction of scar tissue formation 25 . In another study, oral doxycycline was shown to inhibit MMP and improve and the strength of rotator cuff repairs in rats 26 .…”
Section: Introductionmentioning
confidence: 99%